2020
DOI: 10.1109/access.2020.3032795
|View full text |Cite
|
Sign up to set email alerts
|

Building a Fish–Vegetable Coexistence System Based on a Wireless Sensor Network

Abstract: The foremost purpose of this study is to use wireless sensor network (WSN) technology to build an intelligent fish-vegetable coexistence system. As a traditional fish-vegetable coexistence system lacks intelligent diagnoses, personnel and the original materials are difficult to control, and efficiency is low. We expect to remotely monitor the environmental values of the fishvegetable coexistence system at any time through Internet of Things technology and to control the feeding time and the brightness of LED l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…The authors used self-adaptive data fusion via a wireless sensors network to remotely monitor the medical care control system. The results of experiments showed that the system can enable the accurate and stable monitoring of the patient [24][25][26]. It can solve three pressing problems:…”
Section: Round Intersection Positioningmentioning
confidence: 99%
“…The authors used self-adaptive data fusion via a wireless sensors network to remotely monitor the medical care control system. The results of experiments showed that the system can enable the accurate and stable monitoring of the patient [24][25][26]. It can solve three pressing problems:…”
Section: Round Intersection Positioningmentioning
confidence: 99%
“…These controllers will adjust their parameters according to the best living environment for the fish and achieve the most stable and comfortable state. This information is continuously stored in a computer database, allowing users to track and record the growth of their fish [6].…”
Section: Introductionmentioning
confidence: 99%
“…WSNs have sensor nodes of different displacements, which are displaced and isolated, wirelessly connected to each other, and usually connected to the gate nodes [15][16]. The distance between the sensor terminals can range from ten to hundreds of meters depending on the antenna gain, transmission power and operating frequency [17][18][19][20]. The wireless sensor senses the day-to-day weather in live data, which helps farmers monitor the weather.…”
Section: Introductionmentioning
confidence: 99%